2019
DOI: 10.15583/jpchrom.2019.014
|View full text |Cite
|
Sign up to set email alerts
|

Application of Skin Gas GC/MS Analysis for Prediction of the Severity Scale of Parkinson’s Disease

Abstract: Parkinson's disease (PD) is diagnosed by neurological examinations, as well as by scintigraphy for the dopamine transporter and metaiodobenzylguanidine (MIBG). We studied possible application of the skin gas in diagnosis of PD. We analyzed chemical substances emanated from the skin by gas chromatograph/mass spectrometer (GC/MS) after on-line-pre-concentrator. We analyzed the skin gas in 61 PD patients and 61 controls. The GC/MS chromatograms were sectionalized every 30 sec. The retention time drift was shifted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For instance, using GC-MS, Trivedi et al investigated volatile metabolites of sebum samples obtained from PD patients and HCs, revealing the existence of differential sebum VOCs and identifying a distinct volatiles-associated signature for PD [16]. In addition, Tsuda et al used GC-MS to analyze the scent compounds of sebum and found that the types and concentrations of VOCs from PD patient sebum were related to UPDRS-III [17]. Their diagnostic model had a sensitivity of 90.2% and a specificity of 85.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, using GC-MS, Trivedi et al investigated volatile metabolites of sebum samples obtained from PD patients and HCs, revealing the existence of differential sebum VOCs and identifying a distinct volatiles-associated signature for PD [16]. In addition, Tsuda et al used GC-MS to analyze the scent compounds of sebum and found that the types and concentrations of VOCs from PD patient sebum were related to UPDRS-III [17]. Their diagnostic model had a sensitivity of 90.2% and a specificity of 85.2%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Tsuda et al. used GC–MS to analyze the scent compounds of sebum and found that the types and concentrations of VOCs from PD patient sebum were related to UPDRS‐III [17]. Their diagnostic model had a sensitivity of 90.2% and a specificity of 85.2%.…”
Section: Discussionmentioning
confidence: 99%
“…The fast, easy-to-use, and portable AIO system can balance sensitivity, specificity, linearity, dynamic range, detection limit, detection efficiency, and discrimination ability. Compared with the GC–MS, liquid chromatography–MS, or paper spray ionization coupled with ion mobility-MS, the AIO system greatly improves the detection speed and reduces the detection cost. ,,,, Compared with traditional clinical PD diagnosis methods, the AIO system is a fast and noninvasive method. It can also be widely used in hospitals, clinics, and homes as a PD patient screening or family self-health check method.…”
Section: Discussionmentioning
confidence: 99%
“…Trivedi used gas chromatography–mass spectrometry (GC–MS) to prove that there were different VOCs in the sebum of PD and healthy people . These VOCs such as perillic aldehyde and eicosane may change with the increase of sebum secretion, and the interaction between sebum and the yeast of the microbiome can make human skin smelly. Besides, Tsuda used GC–MS to analyze the smell of sebum and found that the types and concentrations of VOCs such as dodecane, acetone, and ethyl acetate released in the sebum of PD patients were related to UPDRS part 3, representing the severity of motor in PD. These studies indicated that sebum gas could be used for the detection of PD.…”
Section: Introductionmentioning
confidence: 99%